Holographic Schwinger Effect in a Confining D3-Brane Background with Chemical Potential - Zi-qiang Zhang; De-fu Hou; Yan Wu; Gang Chen (Advances in High Energy Physics)
Using the AdS/CFT correspondence, we investigate the Schwinger effect in a confining D3-brane background with chemical potential. The potential between a test particle pair on the D3-brane in an external electric field is obtained. The critical field Ec in this case is calculated. Also, we apply numerical method to evaluate the production rate for various cases. The results imply that the presence of chemical potential tends to suppress the pair production effect.